A comparison of stratified sand filters and percolation trenches for on-site wastewater treatment - GILL, LAURENCE; O Súilleabháin, Cormac; Misstear, Bruce Dudley; Johnston, Paul Meredith (My University, 2009)
Two separate on-site wastewater treatment systems were constructed at premises in eastern Ireland, one using a conventional septic tank, the other using a septic tank followed by a naturally aerated peat filter. The respective effluents were then split at each site whereby half was directed into percolation trenches and the other half pumped into intermittently dosed, stratified sand filters for a year. Samples were taken at different depths in the subsoil beneath both the percolation trenches and sand filters and analyzed for chemical and bacteriological determinants. Samples were also taken at different layers within the sand filters, which were tested at various hydraulic loading rates. Although the sand filters require a much smaller surface area, the respective pollutants on each site were attenuated to the same level in the subsoil when compared to the percolation trenches. As a result of the trials, the recommendations for design hydraulic loading rates in Ireland were 30L/m2day for filters receiving septic tank effluent and 60L/m2day for filters receiving secondary treated effluent.
PUBLISHED
Keywords: Wastewater treatment; Ireland; Septic tanks; Filtration; Smart & Sustainable Planet